2022
DOI: 10.1055/a-1807-0336
|View full text |Cite
|
Sign up to set email alerts
|

Early Rhythm Control and the Risks of Ischemic Stroke, Heart Failure, Mortality, and Adverse Events When Performed Early (<3 Months): A Nationwide Cohort Study of Newly Diagnosed Patients with Atrial Fibrillation

Abstract: Background: In EAST-AFNET 4 trial, early rhythm control was associated with better clinical outcomes for patients with atrial fibrillation (AF). However, whether the better outcomes of patients assigned to rhythm control were solely due to “early” intervention or because of more regular and structured follow up was unclear. Objective: To investigate whether the findings of EAST trial are applicable to the ‘real world’ clinical setting, where a less structured management protocol is operated. Methods: From 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…A nationwide cohort study confirmed that on routine daily care, early rhythm control was associated with lower risks of ischemic stroke, heart failure, mortality, and composite adverse events compared with usual care. 25 Interestingly, when early rhythm control was performed earlier (i.e., within the first 3 months after AF diagnosis), the risk of clinical events was lower, and aligned with other studies showing better outcomes in younger patients, with less comorbidities. 26 Combined with opportunistic single time-point screening electrocardiogram, the diagnosis and management of AF could be significantly improved, thereby reducing ischemic stroke rate.…”
Section: Diagnosis and Management Of Atrial Fibrillationsupporting
confidence: 80%
“…A nationwide cohort study confirmed that on routine daily care, early rhythm control was associated with lower risks of ischemic stroke, heart failure, mortality, and composite adverse events compared with usual care. 25 Interestingly, when early rhythm control was performed earlier (i.e., within the first 3 months after AF diagnosis), the risk of clinical events was lower, and aligned with other studies showing better outcomes in younger patients, with less comorbidities. 26 Combined with opportunistic single time-point screening electrocardiogram, the diagnosis and management of AF could be significantly improved, thereby reducing ischemic stroke rate.…”
Section: Diagnosis and Management Of Atrial Fibrillationsupporting
confidence: 80%
“…Patients' original identification numbers have been encrypted in this cohort dataset to protect privacy, but the encrypting procedure was consistent so that a linkage of the claims belonging to the same patient was feasible within the NHI database and can be followed continuously. Details about Taiwan NHIRD have been provided in our previous studies (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and the accuracy of the NHIRD has been validated (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…Six studies assessed ischemic stroke (10,11,(13)(14)(15)17). Early rhythm control was linked to a lower risk of stroke in the patients (RR, 0.77; 95% CI 0.67-0.87; P < 0.0010; I 2 = 64%; Figure 3).…”
Section: Morbiditymentioning
confidence: 99%
“…However, the treatment of AF has changed dramatically since the above RCTs were published. Several studies have recently shown that the incidence of adverse cardiovascular outcomes was reduced by early rhythm control compared with rate control (10)(11)(12)(13)(14)(15)(16)(17). To determine whether early rhythm control is better than rate control in patients with AF, we performed a systematic review and metaanalysis.…”
Section: Introductionmentioning
confidence: 99%